AIRBNB a new marketing strategy for real estate entrepreneurs - Sulaiman, Dr. Noralfishah; Wei, She Teo; Ismail, Prof Dr.Maziah (Malaysian Institue, 2018)
Founded in August of 2008 and based in San Francisco, California, Airbnb is a trusted and reliable online community marketplace for people to list, discover, and book unique accommodations around the world either online or from a mobile phone. Online tools offered by platforms like Airbnb represent an effective virtual place for real estate marketing. Airbnb helps real estate entrepreneurs to monetise their latent spaces by making it easy for them to list and earn rental income. This study aimed at hosts’ perceptions towards Airbnb in Malaysia as a real estate marketing strategy. Objectives of this research are, namely: to study the benefits of using Airbnb and present results to Airbnb hosts in Malaysia, to identify challenges faced by Airbnb hosts in Malaysia and to suggest strategies in optimizing the function of Airbnb as a new real estate marketing strategy in Malaysia. The research methodology that has been used is online interview in order to collect information towards the host perception on Airbnb via email responses. Airbnb has only recently been launched in Malaysia and hence is not yet popular. Therefore, in this study, the establishment of new knowledge in this research area is very important in order to enhance the popularity and growth of Airbnb in Malaysia. It is hoped that this study will promote a new marketing strategy which can be adopted among the real estate entrepreneurs in Malaysia.